Perancangan Aplikasi Untuk Kompresi Ayat-Ayat Di Dalam Qanun Aceh Menerapkan Algoritma Huffman - Ahmad Rafiqi (STMIK Budi Darma, 2021)
The Aceh Qanun data stored in digital form has several advantages compared to printed data, including data that is safe from rodents, data can move around easily, but digital qanuns have problems, there are many articles and verses. paragraph causes the file size to be large so that it uses a very large memory. The solution to the problem above is how large files can be compressed in order to speed up moving and saving the file. The compression of the text file is done by reducing the size of the file by reducing the bits in the saved file. By applying the Huffman algorithm to perform compression techniques, large files will be reduced in size so as to save storage space. In this study, using this algorithm, the compression results will be beneficial in making sending and moving text files easier.